The Effectiveness of Forest Management and Monitoring Implementation under the National Forest Stewardship Standards (NFSS) Scheme in Indonesia - Sarjito, Joko; Budiastuti, Maria Theresia Sri; Hidayat, Agung; Yuswantoro, Ismail Eko; Wintanti, Rizkia Ajeng Setya (Department of Forestry, Faculty of Agriculture, University of Lampung, 2025)
Forest management activities inevitably affect environmental functions and community well-being, necessitating rigorous impact monitoring to improve management practices. The Indonesian National Forest Stewardship Standards (NFSS) provide structured guidelines to balance timber production with environmental protection. This study evaluates the comprehension and application of these standards in forest harvesting planning, implementation, and impact assessment. A quantitative descriptive method was employed, integrating questionnaires, field observations, and interviews with field staff from a Forest Stewardship Council (FSC)-certified forest concession in West Papua, Indonesia. Respondents included staff involved in forest planning, production and logging road construction, silviculture and environmental monitoring, and community development. Data were collected using NFSS-based questionnaires and analyzed using the Likert scale method. In addition, triangulation was conducted via field observations at harvesting sites, document reviews (forest management procedures, High Conservation Value report, Social Impact Assessment report, and Environmental Management and Monitoring Plan report), and interviews to validate questionnaire findings. The results show an average Likert score of 83.91% across five key variables (baseline environmental data, Reduced Impact Logging (RIL) map presence, RIL implementation, human resources, and impact monitoring and adaptation), indicating a strong understanding of NFSS standards. However, challenges remain in enhancing community engagement, implementing best management practices, strengthening supervision and impact monitoring techniques, and developing adaptive strategies for sustainable forest management. Keywords: forest harvesting, forest management, impact monitoring, NFSS Indonesia, reduced impact logging